2021
DOI: 10.1038/s42003-021-02494-3
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations of large-scale brain networks temporal dynamics in young children with autism

Abstract: Autism spectrum disorders (ASD) are associated with disruption of large-scale brain network. Recently, we found that directed functional connectivity alterations of social brain networks are a core component of atypical brain development at early developmental stages in ASD. Here, we investigated the spatio-temporal dynamics of whole-brain neuronal networks at a subsecond scale in 113 toddlers and preschoolers (66 with ASD) using an EEG microstate approach. We first determined the predominant microstates using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 42 publications
(54 reference statements)
3
9
0
Order By: Relevance
“…This may be because the participants involved in the study were all healthy college students. Compared to the subjects with cognitive impairment, the difference in cognitive function of the participants may be much less than that of previous studies (Bochet et al, 2021;Li et al, 2022;Nishida et al, 2013). Meanwhile, this result is in line with the results of Kim et al (2021), who suggest that transition probability can reflect a considerable change in cognition, but is not suitable for reflecting the degree of difference in task performance.…”
Section: Feature Selection and Classificationsupporting
confidence: 78%
“…This may be because the participants involved in the study were all healthy college students. Compared to the subjects with cognitive impairment, the difference in cognitive function of the participants may be much less than that of previous studies (Bochet et al, 2021;Li et al, 2022;Nishida et al, 2013). Meanwhile, this result is in line with the results of Kim et al (2021), who suggest that transition probability can reflect a considerable change in cognition, but is not suitable for reflecting the degree of difference in task performance.…”
Section: Feature Selection and Classificationsupporting
confidence: 78%
“…This lends support to the relative stability of broad microstate topographies across age, despite observations of age-related alterations to specific microstate temporal features such as duration, coverage, and occurrence. Age-related changes in specific temporal parameters of microstates have been previously reported elsewhere (Koenig et al, 2002;Tomescu et al, 2018) and have also been shown be altered across several neurodevelopmental, psychiatric, and neurological illnesses (Andreou et al, 2014;Baldini et al, 2023;Bochet et al, 2021;da Cruz et al, 2020), thus highlighting their clinical relevance. More broadly, these findings appear to parallel previous fMRI work characterising functional brain organisation and development in children spanning a similar ages (e.g., 7-9 years; Supekar et al, 2009).…”
Section: Discussionmentioning
confidence: 56%
“…Prior to running the microstate analyses, the EEG data were bandpass filtered between 1 and 40 Hz (fourth order zero-phase Butterworth filter) and were down-sampled to 250 Hz to reduce computational burden (Bochet et al, 2021). Microstate analysis was conducted in MATLAB implementing the open-source Microstate EEGLAB toolbox (version 1.0) (Poulsen et al, 2018).…”
Section: Microstate Analysismentioning
confidence: 99%
“…The data were filtered again at 2–20 Hz before calculation to remove the effect of high‐frequency noise. The highest spatial correlation was observed to exist between four and six types of microstates during numerous studies, 10 , 23 , 24 , 25 hence this was chosen as the clustering range. The specific process of microstate clustering could be divided into the following three steps.…”
Section: Methodsmentioning
confidence: 99%